Solving the paradox of monetary profits - Steve Keen (Kiel Institute for the World Economy (IfW), 2010)
Bruun and Heyn-Johnsen (2009) state the paradox that economics has failed to provide a satisfactory explanation of how monetary profits are generated, even though the generation of a physical surplus is an established aspect of non-neoclassical economics. They emphasise that our ability to explain phenomena like the Global Financial Crisis (GFC) will be limited while ever we are still unable to explain this fundamental aspect of capitalism. In fact this paradox can be solved very simply, using insights from what is known as Circuit Theory. In this paper the author shows how monetary profits are generated, and introduces a multisectoral dynamic disequilibrium monetary model of production.
Keywords: E12; E17; E20; E51; 330; Endogenous money; circuit theory; Geldtheorie; Kredittheorie; Gewinn; Ungleichgewichtstheorie; Dynamisches Modell; Mehr-Sektoren-Modell; Theorie